PENINGKATAN KEMAMPUAN BERPIKIR KREATIF PESERTA DIDIK MENGGUNAKAN MODEL BLENDED LEARNING BERBANTUAN APLIKASI EDMODO - Siti Khofifah; Yayu Laila Sulastri (Universitas Islam Nusantara, 2022)
This research was motivated by the low creative thinking ability of students in learning mathematics. One alternative learning that can be applied to improve student creative thinking ability is the Blended Learning (BL) model with the help of the edmodo application. The purpose of this study was to see the increase in creative abilities, accountability character, and the relationship between accountability characters and creative thinking ability through the application of the BL model assisted by the Edmodo application. The research method used is a quasi-experimental method. The population in this study were all student of class X in one of the secondary schools in Bandung Regency with a sample of class X IPA 1 as the experimental class and X IPA 2 as the control class. The instrument used was a creative thinking ability test. Based on the results of the Mann Whitney analysis of the creative thinking ability test of students, the increase in creative thinking ability that learn to use the BL model is better for student who use the Discovery Learning Model. The accountability character of students who use the BL model with Edmodo applications has a good interpretation. The accountability character of students has a positive relationship with creative thinking ability and low interpretation.